Knowledge management behavior among academicians: the case of a Malaysian higher learning institution - Mohamed Jalaldeen, Mohamed Razi; Md Habibullah, Md Habibullah; Hussin, Husnayati (Universiti Utara Malaysia Press, 2019)
Proper knowledge management (KM) is vital for any organization to perform to the expectation including higher learning institutions (HLIs). Hence, struggling to perform is an indication of lack of KM initiatives. Though many facets of KM have been investigated in HLIs, more studies are needed as the previous empirical works have focused only on knowledge sharing behavior among academicians. An intensive literature review exposes that nonexistence of works employing KM-related theories. Therefore, this study seeks to investigate academicians’ perceived intention (KM Intention) and involvement in KM initiatives (KM Behavior) and its predictors in a Malaysian HLI, which is struggling to perform, by relating theory of knowledge creation. KM intention explains the perception and the attitudes towards KM while the KM behavior illustrates the real behavior. Both these variables were operationalized based on knowledge creation theory through the socialization, externalization, combination, and internalization (SECI) process. A conceptual framework was developed based on the theory of reasoned action and the theory of planned behavior. Six independent variables representative of the socio-cultural nature of KM - trust, management support, decentralization, IT support, performance expectancy, and effort expectancy - were considered as the predictors of KM intention, which in turn, predict KM behavior. Data were collected from 156 academicians from an HLI in Malaysia using questionnaires. The questionnaire items were adapted from previous studies. The structural model analysis confirmed that out of seven proposed hypotheses, four are supported: Trust, performance expectancy, and effort expectancy influence KM Intention, while KM Intention influences KM Behavior. Even though further research works are needed to generalize the findings, the current research and the findings can enrich the KM literature and provide some insights to the decision makers of the selected HLI on the appropriate KM implementation strategies.